Social Stress, Visceral Obesity, and Coronary Artery Atherosclerosis: Product of a Primate Adaptation - Shively, Carol A. (2009)
Abdominal obesity is prevalent and often accompanied by an array of metabolic perturbations including elevated blood pressure, dyslipidemia, impaired glucose tolerance or insulin resistance, a prothrombotic state, and a proinflammatory state, together referred to as the metabolic syndrome. The metabolic syndrome greatly increases coronary heart disease (CHD) risk. Social stress also increases CHD although the mechanisms through which this occurs are not completely understood. Chronic stress may result in sustained glucocorticoid production, which is thought to promote visceral obesity. Thus, one hypothesis is that social stress may cause visceral fat deposition and the metabolic syndrome, which, in turn increases CHD. CHD is caused by coronary artery atherosclerosis (CAA) and its sequelae. Cynomolgus monkeys (Macaca fascicularis) are a well-established models of CAA. Social subordination may be stressful to cynomolgus monkeys and result in hypercortisolemia and exacerbated CAA in females. Herein is reviewed a body of literature which suggests that social stress increases visceral fat deposition in cynomolgus monkeys, that subordinate females are more likely than dominants to have visceral obesity, that females with visceral obesity have behavioral and physiological characteristics consistent with a stressed state, and that females with high ratios of visceral to subcutaneous abdominal fat develop more CAA. While these relationships have been most extensively studied in cynomolgus macaques, obesity-related metabolic disturbances are also observed in other primate species. Taken together, these observations support the view that the current obesity epidemic is the result of a primate adaptation involving the coevolution with encephalization of elaborate physiological systems to protect against starvation and defend stored body fat in order to feed a large and metabolically demanding brain. Social stress may be engaging these same physiological systems, increasing the visceral deposition of fat and its sequelae, which increase CHD risk.